Psychological factors causing nonadherence to safety regulations in Israel's stone and marble fabrication industry: Unveiling the source of worker noncompliance - Moshe Mishali; Daniel Weiler (Cogent Business & Management, 2017)
Background: Silicosis remains a lung disease which may cause severe incapacitation and even be fatal. We examined why stone processors in Israel, though aware that regular occupational unprotected exposure to harmful silica dust might cause silicosis, choose to work without protection, in defiance of legislation and employer instructions. The study seeks to identify and map the psychological factors that non cooperative processors use, to justify ignoring safety guidelines. Understanding the inner logic behind nonadherence in a scientific and nonjudgmental way could enhance efforts to reduce unsafe behavior among stone and marble processors, including ASW (Artificial Stone Workers). Methods: This qualitative study included semi-structured in-depth interviews with 25 stone processors. The interview transcripts were processed and analyzed by the authors who identified the leading resistance themes underlying noncompliance. Results: The current study found that although interviewees made an initial declarative statement that protection from dust is important due to the perceived and acknowledged danger, as the interview progressed the interviewees displayed increasing reservations, showing that despite their recurrent declarations of understanding the danger of not using protective measures—not all of them do so in practice. Their responses show that the processors have knowledge and awareness of occupational illnesses associated with exposure to silica dust and that they had full access to the relevant protective measures. The responses also reveal the perceptions, personality traits and defense mechanisms around which processors have built a psychological narrative to justify their noncompliant behavior. We found that ASW are well aware of the risks and dangers of their occupation yet they almost completely deny personal responsibility and blame others for the consequences of their behavior (External locus of control). Their predominant emotional reaction was anger. Each worker's response was governed by a “personal and unique narrative” that represents a defense mechanism for nonadherence to safety measures. Conclusions: Given the psychological motivators, the main conclusion of the study is that it takes more than just enhancing the awareness of workers to the importance of using protective measures to create a sustainable change in the safety climate at stone processing plants. Therefore, it is necessary that all players execute their roles in full, in order to ensure that nonadherent behavior is not only acknowledged by fabricators as endangering their health but it has also immediate implications related to their employment, freedom to operate and responsibility.
Keywords: 650